Hematological and Histopathological Effects of Subacute Aconitine Poisoning in Mouse - Lu, Hao; Mei, Li; Guo, Ziyu; Wu, Kexin; Zhang, Yunhao; Tang, Shiyu; Zhu, Yiru; Zhao, Baoyu (Frontiers in Veterinary Science, 2022)
Aconitine is the principal toxic ingredient of Aconitum, which can cause systemic poisoning involving multiple organs and systems after animal ingestion. The purpose of this study was to investigate the effects of aconitine on hematological indices and histological changes in mice. One hundred twenty mice were divided into a control group (normal saline), low-dose group (0.14 µmol/L), middle-dose group (0.28 µmol/L) and high-dose group (0.56 µmol/L), which were continuously lavaged for 30 days. The blood of ten mice were collected randomly and analyzed by group at the 10th, 20th, and 30th days, and some tissues were collected and stained with hematoxylin-eosin to observe histological changes at the 30th day. Compared with the control group, the organ coefficient (%) of liver, spleen, lungs, and brain of the high-dose group were significantly increased (p<0.05 or p<0.01). White blood cells (WBCs) and Granulocyte (Gran) initially decreased and then increased in each poisoning group, with significant differences in the high-dose group (p<0.05 or p<0.01). Red blood cells (RBCs), hemoglobin (Hb), hematocrit (HCT), and blood platelets (PLTs) decreased continuously in all groups except the low-dose group at the 20th and 30th days (p<0.05 or p<0.01). Moreover, blood urea nitrogen (BUN), alanine aminotransferase (ALT) and aspartate aminotransferase (AST) increased in each poisoning group, compared with the control group, with significant differences except for the low-dose group (p<0.05 or p<0.01). Creatinine (CRE) initially increased and then decreased, the total protein (TP) and albumin (ALB) decreased, with significant differences observed in the high-dose and middle-dose groups (p<0.05). All the mice in the poison-treated groups showed varying degrees of histopathological changes such as degeneration and necrosis of tissues. Our data suggest that different doses of aconitine have remarkable effects on hematological and histopathological changes in mice, in a significant time and dose-effect relationship.